Flexible and rapid construction of viral chimeras applied to Hepatitis C Virus - McClure, Patrick C.; Urbanowicz, Richard A.; King, Barnabas J.; Cano-Crespo, Sara; Tarr, Alexander W.; Ball, Jonathan K. (Microbiology Society, 2016)
A novel and broadly applicable strategy combining site directed mutagenesis and DNA assembly for constructing seamless viral chimeras is described using Hepatitis C Virus as an exemplar. Full-length HCV genomic cloning cassettes, which contained flexibly situated restriction endonuclease sites, were prepared via a single site-directed mutagenesis reaction and digested to receive PCR amplified virus envelope genes by In-Fusion cloning. Using this method we were able to construct gene-shuttle cassettes for generation of cell culture-infectious JFH-1-based chimeras containing genotype 1-3 E1E2 genes. Importantly, using this method we also show that E1E2 clones that were not able to support cell entry in the HCV pseudoparticle assay did confer entry when shuttled into the chimeric cell culture chimera system. This method can be easily applied to other genes of study and other viruses and, as such, will greatly simplify reverse genetics studies of variable viruses.